2009
DOI: 10.1007/s11249-009-9492-9
|View full text |Cite
|
Sign up to set email alerts
|

Friction Properties of Carbon Nano-Onions from Experiment and Computer Simulations

Abstract: The carbon nano-onion can be considered as a new kind of interesting lubricating nanoparticle. Used as lubricant additives, carbon nano-onions lead to a strong reduction of both friction and wear, even at low temperature. To better elucidate the mechanisms by which these processes occur, coupled experimental and computational investigations are carried out. In addition, it is found that lubricious iron oxide nanoparticles are generated in the core of the steel contact through mechanisms that are not yet known.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 23 publications
9
43
0
Order By: Relevance
“…For example, Joly-Pottuz et al [264] conducted friction and wear experiments and NEMD simulations of carbon nano-onions (2 nm diameter) between sliding diamond-like carbon (DLC) surfaces at high contact pressure (1−5 GPa). Both the experiments and simulations suggest that the carbon nano-onions remained intact under compression and sliding and did not exfoliate to graphitic planes [264], unlike MoS 2 fullerenes [263]. Further simulations by Bucholz et al [265] indicated that the ability of the nano-onions to roll is inhibited both by increased contact pressure and the presence of a diamond core within the nanoparticles.…”
Section: Nanoparticles As Dry Lubricantsmentioning
confidence: 99%
“…For example, Joly-Pottuz et al [264] conducted friction and wear experiments and NEMD simulations of carbon nano-onions (2 nm diameter) between sliding diamond-like carbon (DLC) surfaces at high contact pressure (1−5 GPa). Both the experiments and simulations suggest that the carbon nano-onions remained intact under compression and sliding and did not exfoliate to graphitic planes [264], unlike MoS 2 fullerenes [263]. Further simulations by Bucholz et al [265] indicated that the ability of the nano-onions to roll is inhibited both by increased contact pressure and the presence of a diamond core within the nanoparticles.…”
Section: Nanoparticles As Dry Lubricantsmentioning
confidence: 99%
“…Specifically, CNO has been shown to reduce the friction coefficient by &85 % when used as a solid lubricant [22]. Friction coefficient reductions of &50 % have also been observed compared to a pure base oil when CNO [23] and CND [12] were used as additives. Under high-pressure boundary lubrication conditions, much of the base oil is squeezed out from between asperities [27,28], leading to contact of opposing surfaces and high friction and wear.…”
Section: Introductionmentioning
confidence: 99%
“…Large friction and wear benefits can still be observed when CNO and CND are used as additives, suggesting that they are able to reduce the contact of asperities more effectively than the base oil alone [12]. In comparative studies, CNO additives have yielded both lower [19,23] and higher [17] friction and wear than CND additives, though the reasons for this disparity are, prior to this study, yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, there is the difference between the behavior of wear particle which may contribute to the formation of the graphitization layer in pure-PAO and GMO solution as shown in Fig 12. The graphitization layer which can be composed of the wear particles of the ta-C film formed on the edge of wear scar for pure-PAO, whereas the wear particles were dispersed well in the solution for PAO + GMO. It is well known that carbon nano-particles such as carbon nano-tube, carbon nano-onion and graphene can be dispersed in oils by the functional group-modified technics [39]. It is assumed that GMO adsorbed on the wear particles derived from the ta-C film, and GMO worked as functional group to disperse the wear particles in the solution.…”
Section: Discussionmentioning
confidence: 99%